Manajemen Hubungan Masyarakat Dalam Pandangan Al Qu’ran - Arianto (Proceedings of Annual Conference on Islamic Educational Management, 2021)
Public relations with certain institutions, especially educational institutions, is a deliberate effort, planned continually to establish and foster mutual understanding between the organization of educational institutions and Society. Public relation is a center of activities that covers many areas and efforts that are integrated with the community. The covering the work relationship between human scope, human relationships with social media and tools, expertise in using it and selecting communication tools and The right mass media.